COMPARISON OF VISION OUTCOMES BETWEEN SICS (SMALL-INCISION CATARACT SURGERY) AND PHACOEMULSIFICATION IN CATARACT SURGERY - SAI K, NAVYA; REDDY C, SUHAS; K, SRILEKHA; PRIYA K, AVANTHI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The main objective of the study is to compare the vision outcomes between small-incision cataract surgery (SICS) and phacoemulsification (PHACO) procedures, to compare the quality of life (QOL) before surgery and after surgery, to improve the patient’s knowledge of their disease condition, and to increase medication adherence after the surgery. Methods: A prospective observational study was conducted for 6 months. About 100 patients were enrolled in the study according to the study criteria. Different scales ([visual function questionnaire] VFQ 25, QOL scale [QOLS] by Schalock and Keith, Morisky Adherence Scale -8 items) were scored from the patient’s profile and treatment chart by communicating with physicians, counseling the patients. Results: One hundred patients were assessed before and after cataract surgery and follow-up was made for 1 month. Overall, vision-related QOL was significantly improved in PHACO than SICS patients. National Eye Institute VFQ 25 was assessed on day 7 and day 30 where we have observed a statistically significant improvement in the PHACO group of patients than in SICS. Their medication adherence scores were categorized into a high, medium, low category, and most of the SICS patients remained in the medium category, whereas the number of patients increased from medium to high category in PHACO patients. Conclusion: We concluded that PHACO is better than small incisional cataract surgery due to its small and self-sealing incision, which requires no stitches in most cases, with minimum complications the patient heals faster and recovers rapidly.